Analysis of Aggregate Herding Behavior in the Capital Market: Evidence from Indonesia and Singapore - Gusni, Gusni; Nugraha, Nugraha; Disman, Disman; Chochole, Tomas (Media Ekonomi dan Manajemen, 2023)
The high uncertainty in the capital market due to some crises that hit the world over the last few decades has the potential to cause herding behavior in the aggregate capital market, both in developed and emerging capital markets. The main objective of this study is to detect the existence of herding behavior, including asymmetric herding and global factor drives (oil prices and fed fund rates) on aggregate herding behavior in the Indonesian and Singapore capital markets during the period Jan 2015 to December 2020. This study employs a cross-sectional dispersion approach to achieve study goals. Research findings denote aggregate herding behavior occurs only in the Singapore capital market, while in Indonesia no herding behavior is detected. Asymmetric herding testing for both capital markets revealed no herding tendency in up and down market conditions. This condition implies that low volatility cannot ensure the absence of aggregate herding behavior. Global factors have proven to significantly drive herding behavior in the Singapore capital market, while in Indonesia it is only the oil price. The findings of this study will provide information that policymakers can use to maintain capital market stability in both countries.